Identifying the nuclear localization signal of the Arabidopsis thaliana MADS box transcription factor Flowering Locus C - Wiseman, Brittany (My University, 2021)
The goal of this project is to design a research strategy to identify the Nuclear Localization Signal (NLS) of the Arabidopsis thaliana MADS box transcription factor Flowering Locus C (FLC), and to make plant transformation components that are necessary for the creation of controls for this objective. An NLS is required for the nuclear localization of nuclear proteins, and though previous work on Arabidopsis has established conserved structural-functional domains within FLC, the NLS has not yet been characterized. To complete the objectives of this project, primers were designed and used to modify FLC to be compatible with the GreenGate cloning system. FLC was cloned, sequenced, and glycerol stocks were created and stored. Future projects will use this FLC to create an FLC:GFP fusion to serve as a control where protein localization is expressed in the nucleus. Electrocompetent Agrobacterium tumefaciens were made and a pGFPGUSPLUS plasmid was introduced. Glycerol stocks were stored to be used in Agrobacterium mediated transformation in the future, which will establish another control line of Arabidopsis expressing GFP proteins that are not nuclearly localized. Finally, a literature review was completed to explore the existing understanding of NLS structure in general and in MADS box transcription factor proteins, to propose mutations that might disrupt the NLS sequence within FLC. This work aims to fill a knowledge gap in regards to the mechanism of nuclear localization of FLC and will ultimately contribute to our understanding of nuclear localization in plants and MADS box proteins in general.
Presented virtually at: Student Research Day (April 26, 2021, MacEwan University, Edmonton), Undergraduate Research in Science Conference of Alberta ( May 3-4, 2021, Concordia University, Edmonton), National Undergraduate Genetics Symposium (May1-2, 2021), and the Richard E. Peter Biology Conference (March 1-5, 2021, University of Alberta, Edmonton).
Keywords: nuclear localization signals (NLS); Flowering Locus C (FLC)